The link between springtime total ozone and summer UV radiation in Northern Hemisphere extratropics. Issue 15 (1st August 2013) - Karpechko, A. Yu.; Backman, L.; Thölix, L.; Ialongo, I.; Andersson, M.; Fioletov, V.; Heikkilä, A.; Johnsen, B.; Koskela, T.; Kyrölä, E.; Lakkala, K.; Myhre, C. L.; et al.
Abstract : [1] The link between stratospheric ozone decline and ultraviolet (UV) radiation increase at the Earth's surface is well established. In the Northern Hemisphere extratropics, stratospheric ozone is accumulated from autumn to spring as a result of transport from its source region in the tropics. The amount of accumulated ozone varies from year to year due to natural dynamical variability and chemical destruction by natural and anthropogenic substances. Observational and modeling studies show that these total ozone anomalies persist in the extratropics from spring to summer. Here we analyze time series of ground‐based UV measurements and satellite retrievals of total ozone and UV radiation and demonstrate that there is a strong link between springtime total ozone and summer UV anomalies in the Northern Hemisphere extratropics. In some regions, the interannual variability in springtime ozone abundance explains 20–40% of the summer UV variability, and this relation can be used for improving seasonal UV forecasts. Using chemistry transport models, we estimate the influence of polar chemical ozone loss on the summer UV north of 35°N. We estimate that the massive Arctic ozone depletion 2011 increased the March–August cumulative erythemal clear‐sky UV dose in the Northern Hemisphere extratropics by 3–4% compared to the climatology, with about 75% of the increase accumulated after the breakup of the polar vortex. This result strongly suggests that the effect of seasonal ozone anomaly persistence should be included in the assessment of the impacts of polar ozone losses. Key Points: Spring total ozone impacts summer UV radiation in the Northern Hemisphere Arctic ozone loss impacts summer cumulative erythemal UV dose in NH Seasonal ozone anomaly persistence can be used for seasonal UV forecasts